Analysis of the precipitation and cloudiness associated with COLs occurrence in the Iberian Peninsula - Nieto, R.; Gimeno, Luis; Añel, J. A.; Torre, L. de la; Gallego, D.; Barriopedro Cepero, David; Gallego, M.; Gordillo, A.; Redaño, A.; Delgado, G. (Meteorology and Atmospheric Physics, 2007)
© Springer-Verlag 2006. This work was supported by the Spanish Ministry of Science and Technology (MCYT) under Grant REN2002-04558-C04- 01=02=03=04 and by the Galician Programme of Research and Development under Grant GIDIT03PXIC38301PN. This work was supported also by a postdoctoral fee (SFRH= BPD=22178=2005) to the principal author from the FCT of Portuguese Ministry of Science, Technology and Education. The authors wish to thank the Spanish National Meteorology Institute (INM) for providing the data analysed in this study. The Iberian Peninsula is one of the regions in the world with higher occurrence of cut-off low systems (COL). The aim of this paper is to analyse the weather events (rainfall and cloudiness layer) associated to COLs in the Iberian Peninsula with tools not previously used: (a) the use of the new multidecadal COLs database developed by Nieto et al (2005) that permit us to study a 41 years period (1958-1998), (b) the checking of the expected weather events (rainfall and cloudiness layer) associated with COLs in a conceptual model (Winkler et al, 2005) and (c) the extensive use of radiosoundings to analyse convective instability in areas inside and close to the COL. Two points of view are used to make the analysis: (1) a source oriented method, when a particular COL is followed and its associated precipitation and cloudiness is analysed over four quadrants in which Iberia was divided and (2) a receptor oriented method, when the precipitation associated to COLs is analysed in given areas, defined by patterns of precipitation. Results reveal that the precipitation and cloudiness patterns associated to COLs in the conceptual model reproduce quite well the main characteristics found over the Iberian Peninsula. The generalized idea that most of the COLs produce intense convective rainfall is show to be misleading. Convective phenomena are important usually when the centre of the COL is located on the Mediterranean region. Most of the rainfall associated with COLs comes from the baroclinic shield; ...